Feminist Praxis: The Michigan Meeting on Ending Gender-Based Violence. Issue 3 (August 2019) - Larance, Lisa Young; Armstrong, Elizabeth A.; Munro-Kramer, Michelle; Sheridan-Fulton, Emily; Kusunoki, Yasamin; Ngo, Quyen; Fincher, Sharron; Denson, Nicole
Feminist praxis in conference planning and implementation may be a promising approach to addressing the complex issue of gender-based violence in an academic setting. This "In Brief" provides an overview of how the Michigan Meeting on Ending Gender-Based Violence planning committee at the University of Michigan embraced feminist praxis by foregrounding diversity in conference presenters and topics presented; structuring the conference's formal and free spaces; creating an inclusive, trauma-informed space where participants and presenters felt welcome; and highlighting participant feedback. By design, this focus in conference planning and implementation enabled tensions to surface between community-based practitioners and university-based researchers, while encouraging the formation of trust. The interdisciplinary conference structure also promoted and made possible greater connections and opportunities for networking and brainstorming on potential future programs and projects. Overall, the outcomes of this conference were positive and show that engagement and participation of community-based practitioners in traditionally academic settings leads to more nuanced discussions necessary for effectively addressing and, hopefully, ending gender-based violence.